2021
DOI: 10.1016/j.bbadis.2021.166097
|View full text |Cite
|
Sign up to set email alerts
|

PPARs in liver physiology

Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors and transcriptional modulators with crucial functions in hepatic and whole-body energy homeostasis. Besides their well-documented roles in lipid and glucose metabolism, emerging evidence also implicate PPARs in the control of other processes such as inflammatory responses. Recent technological advances, such as single-cell RNA sequencing, have allowed to unravel an unexpected complexity in the regulation of PPAR expression, activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 167 publications
1
35
1
Order By: Relevance
“…Although PPARδ agonists have not yet been tested in outcome trials, all PPARs might affect CVD and heart failure through complex systemic actions that modulate cardiovascular risk factors and improve NASH, which is an increasing health problem and a cardiovascular risk factor 172 . Interestingly, several dual-PPAR and pan-PPAR agonists are being tested in clinical trials, currently mainly in patients with NAFLD 173 .…”
Section: Future Directionsmentioning
confidence: 99%
“…Although PPARδ agonists have not yet been tested in outcome trials, all PPARs might affect CVD and heart failure through complex systemic actions that modulate cardiovascular risk factors and improve NASH, which is an increasing health problem and a cardiovascular risk factor 172 . Interestingly, several dual-PPAR and pan-PPAR agonists are being tested in clinical trials, currently mainly in patients with NAFLD 173 .…”
Section: Future Directionsmentioning
confidence: 99%
“…Moreover, it has been shown that retinol promotes normal growth and development of the host ( 38 ). PPAR signaling pathway regulates the expression of genes associated with lipid metabolism, fat formation, maintenance of metabolic homeostasis, and inflammation ( 39 ). Therefore, GAT-2 might regulate excessive fat deposition and inflammation in the livers of female mice, whereas GAT-2 could affect normal growth and development of livers in male mice involving retinol metabolism and PPAR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptors (PPARs) alpha (PPARα, Chr 22) and gamma (PPARγ, Chr 3) are ligand-activated transcription factors of the nuclear receptor superfamily. PPARs are activated by unsaturated fatty acids and form heterodimers with retinoid X receptors (RXRs) to regulate the peroxisomal beta-oxidation of fatty acids [ 108 ]. PPARα promotes fatty acid oxidation, and PPARγ increases lipogenesis and adipogenesis.…”
Section: Genetics Of Ldl Cholesterol In the Big-data Eramentioning
confidence: 99%